Comparison of Generation Z Leadership Styles in Makassar and Surabaya: A Contextual Study in the Accounting Profession - Reswari, Pingkan Ardha; Habiburrochman, Habiburrochman; Hirman, Akhmad Akram; Supratiwi, Wiwik (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study explores the leadership styles of Generation Z professionals in the accounting and finance sector in two major Indonesian cities, Makassar and Surabaya. Using a qualitative approach with thematic analysis, data were collected through semi-structured interviews with ten informants, including accounting staff, tax consultants, and auditors. The findings reveal that Generation Z leaders in both contexts demonstrate democratic, participatory, and situational leadership styles characterized by openness, collaborative decision-making, and the integration of digital technology into workplace practices. Despite cultural differences between Makassar and Surabaya, consistent leadership patterns emerged, particularly in valuing fairness, transparency, and inclusivity in financial reporting and team management. The study contributes to the growing literature on intergenerational leadership by offering insights into how Generation Z’s digital orientation and collaborative values shape organizational practices. Practically, the results highlight the importance of organizations to foster inclusive work environments, leverage technology, and encourage active participation from younger professionals. The research also identifies limitations related to sample scope and cultural depth, suggesting opportunities for broader, cross-sectoral, and cross-cultural studies in the future.